Sterile Caliper Anterior Chamber Decompression Mitigates Intraocular Pressure Spikes in Intravitreal Injections - Mansoor, Mahsaw; Ahmad, Noor-Us-Sabah; Ahmed, S. Bilal; Tadros, Samuel; Folk, James; Abramoff, Michael D. (Translational vision science & technology, 2024)
To investigate the efficacy of a novel approach using a sterile caliper for anterior chamber (AC) decompression in reducing post-intravitreal injection (IVI) intraocular pressure (IOP) spikes. A prospective interventional case series conducted at the Iowa City Veterans Affairs Medical Center (VAMC) with Institutional Review Board approval. Patients were randomized to receive conventional IVI or IVI with sterile caliper decompression. Fifty eyes from 47 patients underwent IVI for various retinal pathologies. Subjects were randomly assigned to the intervention or control arm. Two resident physician providers performed injections, with one applying sterile caliper decompression (intervention) and the other following the standard technique (control). Baseline and postinjection IOP were measured using Tonopen (Reichert, Depew, NY). In both groups there was a significant IOP rise following IVI (P < 0.0001). There was no significant difference in baseline IOP between groups (P = 0.082), but postinjection IOP was significantly lower in the intervention group (23.52 ± 5.98 mm Hg) compared to the control group (44.08 ± 8.48 mm Hg). There were no patients with an IOP spike >25 mm Hg in the intervention arm. The technique was effective regardless of lens status. Sterile caliper AC decompression significantly reduced post-IVI IOP spikes presenting an efficient and cost-effective alternative to previously proposed methods of IOP reduction. Further studies are warranted to validate these findings and explore broader applications in ophthalmic interventions. The caliper decompression technique presents potential benefit in preventing short-term morbidity associated with IOP spikes after IVI and addressing long-term concerns in patients with pre-existing glaucoma.